On the contents and scope of the medical subject “Traumatology and Orthopaedics” - Shymon, Vasyl; Vasilinets, Mykhaylo; Boldizhar, Оleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article analyses the problem of teaching of orthopaedics and traumatology in higher medical schools ofUkraine. Parallels with European educational institutions are drawn. The authors give their recommendations for improving the process of training in the above speciality at relevant departments.